Pharamacognostical and biological studies of trachelospermum jasminoides L : Star jasmine - Family : Apocynacae - Noha Mohamed Elaskary; Maha Mahmoud Salama; Ola Mohamed Mousa; Seham Salah Eldin Elhawary (Cairo : Noha Mohamed Elaskary, 2012)
Part 1 : Botanical study and DNA fingerprint : macromorphological , macromorphological study and DNA fingerprint of the plant . Part 2 : Phytochemical study : preliminary phytochemical screening , investigation of the ethyl acetate , chloroform extracts of the aerial parts , qualitative analysis of the ethanolic extract of the aerial parts by LC - ESI / MS technique , the lipioidal content , investigation of the volatile constituents extracted from the flowers , study of the mineral content
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Pharmacognosy
Issued also as CD
Keywords: Botanical and DNA fingerprint; Phytochemical screening; Review of literature